Generating a proteomic profile of neurogenesis, through the use of human foetal neural stem cells - Garnett, Shaun (Department of Biological Sciences, 2020)
Introduction Neurogenesis, the development of new neurons, starts soon after the formation of the neural tube and is largely completed by birth. Development of the brain after birth is mainly reliant on the formation of new connections between surviving neurons. However, adult neurogenesis does continue in the subgranular zone of the hippocampus from quiescent adult neural stem cells. Traditionally neural stem cells were cultured as neurospheres, a heterogeneous agglomeration of neural cells at various stages of differentiation. This heterogeneity prevented accurate quantitative analysis. In 2008 Sun et al produced the first non-immortalised human foetal neural stem (NS) cell line from nine week old human foetal cortex. These cells are cultured as monolayers, have a radial glia like appearance, self renew and form all three neural cell types, neurons, astrocytes and oligodendrocytes upon differentiation. More recently human foetal neuroepithelial like (NES) stem cells have been produced from five week old human foetal hind-brain, they resemble neuroepithelial cells, with characteristic rosettes, upon differentiation they appear to form a pure population of neurons. These homogeneous monolayer cultures enable quantitative proteomic analysis, to increase our understanding of early brain development Methods Three NES and two NS cell lines were available for analysis. They proliferate by stimulation from FGF and EGF, removal of these growth factors results in spontaneous differentiation. Proliferating NES and NS cells were compared using SILAC labelling. In addition, each cell line was differentiated for 12 days, 6 timepoints were taken and compared using label free quantitation. Results 4677 proteins were quantitated with 473 differentially expressed, revealing fundamental differences between NES and NS cells. NES cells are less differentiated, expressing SOX2 and LIN28, have active cell cycle processes, DNA elongation, histone modification and miRNA mediated gene silencing. Whereas NS cells are more developmentally defined, express multiple membrane proteins, have activated focal adhesion, thereby increasing their binding and interaction with their environment. NS metabolism is more oxidative, utilises lipid metabolism, the pentose phosphate pathway and produces creatine phosphate. Upon differentiation the cell cycle processes are downregulated and neurogenic and gliogenic processes increased. Conclusion This work represent a detailed in vitro characterisation of non immortalised human foetal neural stem cells, it describes the regulatory, metabolic and structural changes occurring within neural stem cells in early brain development. The information herein points towards de-differentiation potentially through LIN28-let7, as a means to produce more neurogenic neural stem cells in vitro thus aiding regenerative therapies, as well as provides a wealth of information for better understanding neurological developmental disorders.